Impact of changes in transport infrastructure on the social infrastructure system of the Ipoly valley - Feketéné Benkó, Kata (Studia Mundi – Economica, 2021)
Transport is as old as humanity, and the development of society, technology and transport has changed in parallel and interdependence. The basic task of transport is to change location, as an economic link, and to act as a mediator. For a long time, transport was also a channel of communication, so its importance cannot be questioned. Today, it can be observed that, despite the fact that virtual space can replace almost all areas of communication, it cannot replace personal appearance and personal relationships. In the absence of these, the relations between them change, become incomplete.Urban external links are made possible by transport corridors, with the largest number of interactions between pairs of settlements connected by bridges in areas separated by rivers, which affect social, including family, kinship relationships, but create local, commercial and economic districts.As long as most domestic infrastructure developments do not necessarily require a thorough justification and investigation for the construction of a new bridge, the cross-border structure needs to be supported for a number of reasons – partly because, where a bridge once stood, society needs to restore connectivity, but the resources needed to do so are not adequately available. One of the simplest and most tangible is the significant increase in the number of additional roads due to the lack or lack of road links between municipalities, as a measure of road network shortages. The indicator only shows the additional need for travel, does not refer to any other factor that may be taken into account, so it is a raw data in itself. In the case of the Ipoly River, it is necessary to examine the network deficit indicator on a historical scale: how this number has evolved between municipalities in about a century.